2016
DOI: 10.3803/enm.2016.31.1.142
|View full text |Cite
|
Sign up to set email alerts
|

Thyrotoxic Periodic Paralysis and Polymorphisms of the ADRB2, AR, and GABRA3 Genes in Men with Graves Disease

Abstract: BackgroundThyrotoxic periodic paralysis (TPP) is a rare complication of thyrotoxicosis characterized by acute attacks of muscle weakness and hypokalemia. Recently, variation in several genes was suggested to be associated with TPP. This study evaluated the genetic predisposition to TPP in terms of the β2-adrenergic receptor (ADRB2), androgen receptor (AR), and γ-aminobutyric acid receptor α3 subunit (GABRA3) genes.MethodsThis study enrolled 48 men with Graves disease (GD) and TPP, and 48 GD patients without TP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The hyperthyroid state may confer a genetic predilection to abnormal electrical potential in muscles, leading to accelerated intracellular shifts of potassium [23]. To define the genetic susceptibility to TPP, we previously evaluated several genes that are associated with androgen receptors and adrenergic receptors [14]. However, we could not demonstrate any significant associations with TPP.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The hyperthyroid state may confer a genetic predilection to abnormal electrical potential in muscles, leading to accelerated intracellular shifts of potassium [23]. To define the genetic susceptibility to TPP, we previously evaluated several genes that are associated with androgen receptors and adrenergic receptors [14]. However, we could not demonstrate any significant associations with TPP.…”
Section: Discussionmentioning
confidence: 82%
“…43 male GD patients with TPP were recruited and 40 male GD patients without TPP were recruited as controls between 2001 and 2006 at Asan Medical Center, Seoul, Korea. GD was diagnosed on the basis of the presence of a diffuse goiter, positivity for one or more anti-thyroid antibodies, suppressed serum TSH levels, and increased serum free T4 levels, as previously described [14]. Patients with TPP displayed acute muscle weakness and hypokalemia in a thyrotoxic state.…”
Section: Subjectsmentioning
confidence: 99%
“…GD is an autoimmune disorder where autoantibodies target antigens expressed in thyroid tissues and hence hyperthyroidism is promoted. 14,19,20 Consensus has been reached that several genetic and environmental factors would affect GD. 2,14 On the other hand, there has been evidence suggesting that part of untreated GD patients tend to suffer from LD.…”
Section: Discussionmentioning
confidence: 99%
“…RAI therapy and low initial titers of thyroglobulin (Tg) and anti-Tg antibody were significant protective factors against disease recurrence among low-risk PTC patients. Park et al [4] evaluated the genetic predisposition to thyrotoxic periodic paralysis (TPP) in terms of the β2-adrenergic receptor, androgen receptor, and γ-aminobutyric acid receptor α3 subunit genes and found no associations of these polymorphisms with TPP. In another article, doctors from the University of the Philippines also reported that fixed-dose radioiodine was associated with a significantly lower incidence of persistent hyperthyroidism at 6 months after radioactive therapy for the treatment of Graves disease [5].…”
Section: Articles On Thyroid Diseasementioning
confidence: 99%